2022
DOI: 10.3390/su14148476
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Factors Affecting the E-Commerce Sustainability of Thai Micro-, Small- and Medium-Sized Enterprises (MSMEs)

Abstract: It is anticipated that e-commerce will contribute to achieving the 17th Sustainable Development Goal, which seeks to improve implementation mechanisms and revitalize global partnerships for sustainable development. However, MSMEs still face a digital gap compared to large enterprises, which affects their e-commerce sustainability. The study’s objective is to examine the factors and barriers affecting the e-commerce sustainability of Thai micro-, small- and medium-sized enterprises (MSMEs) based on a survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 66 publications
1
24
0
1
Order By: Relevance
“…Correspondingly, Yusgiantoro et al (2019) opined that MSMEs with older owners tend to detain the adoption of e-commerce. This was also concurred by Amornkitvikai et al (2022) who concluded that the owner's age can significantly affect MSMEs' adoption of IT and e-commerce. They also posited that older owners are less likely to adopt e-commerce than younger ones because of their limitations in implementing new technologies for their companies.…”
Section: Respondents Of the Study -supporting
confidence: 53%
“…Correspondingly, Yusgiantoro et al (2019) opined that MSMEs with older owners tend to detain the adoption of e-commerce. This was also concurred by Amornkitvikai et al (2022) who concluded that the owner's age can significantly affect MSMEs' adoption of IT and e-commerce. They also posited that older owners are less likely to adopt e-commerce than younger ones because of their limitations in implementing new technologies for their companies.…”
Section: Respondents Of the Study -supporting
confidence: 53%
“…[30] examined the factors and barriers affecting the eCommerce sustainability of Thai retail and food and beverage (F&B) service SMEs in metropolitan Bangkok by applying the TOE framework. The findings by Amornkitvikai et al, [40] are that internal eCommerce tools (i.e. smartphones and websites) and external eCommerce platforms (i.e.…”
Section: Behavioural Factorsmentioning
confidence: 97%
“…In Thai context, Amornkitvikai et al, [40] noted that SMEs are still facing serious challenges in eCommerce development as compared with large enterprises. [30] examined the factors and barriers affecting the eCommerce sustainability of Thai retail and food and beverage (F&B) service SMEs in metropolitan Bangkok by applying the TOE framework.…”
Section: Behavioural Factorsmentioning
confidence: 99%
“…The E-commerce adoption by Thailand's small and medium enterprise exporters has no significant positive impact on export intensity (Ueasangkomsate, 2015), but business-to-business (B2B) e-commerce can increase Thailand's small and medium enterprise exports, while older small and medium enterprise entrepreneurs tend to ignore e-commerce (Amornkitvikai et al, 2022). Meanwhile, Hasan et al (2021) found a low level of e-commerce adoption, where most businesses use conventional patterns to sell goods and services to small and medium enterprises in Indonesia.…”
Section: Introductionmentioning
confidence: 99%